Peningkatan Efisiensi Work Cell Inductive Sensor untuk Produk SINBA pada PT Schneider Electric Manufacturing Batam - Rebecca Yapilando; Tanti Octavia (Jurnal Titra, 2013)
This research is originated from a problem of low efficiency level that happened in SINBA production line at PT Schneider Electric Manufacturing Batam (PT SEMB). Method used for this project is called waste analysis. Waste analysis is a step of analyze to find what kind of waste that actually happen, in order to find any proper improvement to reduce that waste. Observation has been made and the result was showing that the source of the problem is on the work cell layout and ineffective ways of set-up. Many waste happened due to excessive invaluable movement and long set-up time (movement waste and set-up waste). Improvement and solution has been proposed to remove the movement waste. Improvement result showed that efficiency has increased by 4.35%.